Research on the impact of official type and officiating expertise on visual tracking performance: based on the multiple identity tracking task - Rishu Wang; Yidong Wu; Qi Zhang (Frontiers in Sports and Active Living)
IntroductionRecent studies highlight the significance of visual cognition in sports officiating. This study investigates how official type and officiating expertise influence visual tracking performance using the Multiple Identity Tracking (MIT) and dot-detection tasks.Methods36 officials aged 20–38 years were recruited and classified into interactors (basketball referees), reactors (badminton judges), and monitors (gymnastics judges) according to official type, and into expert and non-expert groups according to officiating expertise.ResultsResults revealed significant main effect of official type on tracking accuracy (P < 0.001), detection stimulus awareness rate (P < 0.05), and tracking time (P < 0.001). Officiating expertise had a significant effect on tracking accuracy (P < 0.05), and detection stimulus awareness rate (P < 0.001). Notably, their interaction effect was not significant. Pearson's analysis revealed a positive correlation between the detection stimulus awareness rate and tracking accuracy, but not between tracking time and tracking accuracy.DiscussionResearch suggests that officiating activities are closely related to visual cognition. Reactors demonstrate the advantage of objective fact-based decision making and their officiating characteristics are capable of exhibiting excellent visual performance in the MIT and dot-detection tasks. Furthermore, expert officials with the advantage of systematic training and a high level of officiating expertise, possess excellent visual tracking ability and decision-making skills in specific sports tasks.